Abnormalities of oesophageal mechanoreceptors in canine acrylamide neuropathy. - Satchell, P M (1984)
Dogs exposed to acrylamide develop peripheral neuropathy and megaoesophagus. The properties of slowly adapting oesophageal mechanoreceptors were studied in six control and five acrylamide affected greyhounds in which the oesophagus had been surgically isolated under anaesthesia and oesophageal pressure was controlled while monitoring impulses in oesophageal afferent fibres in the cervical vagus. In the acrylamide affected animals oesophageal afferent units had elevated thresholds and significantly reduced firing rates during ramp increases in oesophageal pressure. It is concluded that abnormalities of oesophageal mechanoreceptors may be important in the pathogenesis of certain oesophageal motility disorders in man and animals.